INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA - Wijaya, Rahmat; Puspita Sari, Rika; Murniati, Sri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
Indonesian as a source of character education need not doubt its existence, because in the Indonesian language the requirement of education values which is the main substance of character education. Character education extracted from the substance of the Indonesian language can be a pillar of nations character education. Character education as a pillar of national character education, today becomes very important, because character education is crucial to the progress of civilization of the nation, which is not only superior, but also intelligent. The superiority of a nation lies in thinking and character. Both types of advantages can be built and developed through education. Therefore, the goal of education is not only intelligence and intelligence (thought), but also moral and character, character, values, and personality are strong, superior and noble (character). In other words, between thought and character must be a unified whole. The realization of the nations character education excavated from Indonesian language sources can be started from the education community through Indonesian language learning. In learning Indonesian language, it should be able to take place through the learning process on every basic competency taught and each indicator of learning outcomes to be achieved.